(untitled) (Anwer Khan Modern Medical College Journal, 2015)
Background: The purpose of this study was to assess drug addiction pattern and knowledge on HIV/AIDS among male addicted undergoing rehabilitation. Methodology: A cross sectional descriptive study was conducted among purposively selected 100 drug addictors in a selected hospital. Pretested semistructured questionnaire was used to collect data by face to face interview. Result: Mean age of respondents was 34.02+_7.12 years. Result showed that about 39.8% of the respondents were addicted due to their friends incitement. More than half (61%) of the drug addicts were taken both Heroin and Injection (narcotics). About 82% of the respondents were never sold blood and 18% were sold their blood due to addiction. More than half (58%) of the respondents were taken sex with residential & commercial sex workers and 27% were taken sex only with their wives. Only 15% had no sexual activity. And more than half (57%) of the respondents did not use condom and 36% were used condom occasionally during their sexual activity. Only 7% used condom regularly. Besides study found that more than 97% of the respondents had knowledge on HIV/AIDS. Only 3% never heard about HIV/AIDS. Result found that 81.4% of the respondents had knowledge on the severity of HIV/AIDS disease and 18.6% did not know. About 89.7% of the respondents said that they had knowledge on transmission of HIV/AIDS through needle sharing and 10.3% did not know. Majority of the respondents 75% had knowledge to prevent HIV/AIDS more than one reason whereas 15.2% showed other reasons. Conclusion: Further large scale study should be conducted and the study result should not be generisable. Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 5-9